2016
DOI: 10.1111/psj.12167
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Policy Advocacy Organizations and Their Theoretical Affinities: Evidence from Q‐Methodology

Abstract: Policy advocacy is an increasingly important function for many nonprofit organizations, yet their advocacy activities have largely escaped theoretical grounding. The literature on nonprofits has described how they engage in policy advocacy, without linking them to theories of policy change. The policy studies literature, on the other hand, has explained how various forms of influence result in policy change, but has largely ignored organizational perspectives on those processes. These two literatures remain la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
(75 reference statements)
0
18
0
Order By: Relevance
“…Inside strategies are often used by business or private interest groups, and outside strategies are often used by public interest groups (Betzold, 2013; Binderkrantz, 2008; Kollman, 1998). A recent study showed that nonprofit organizations will use both inside and outside strategies to advocate for policy change (Gen & Wright, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Inside strategies are often used by business or private interest groups, and outside strategies are often used by public interest groups (Betzold, 2013; Binderkrantz, 2008; Kollman, 1998). A recent study showed that nonprofit organizations will use both inside and outside strategies to advocate for policy change (Gen & Wright, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…There are a variety of policy theories that can be drawn from; however, we highlight a few to illustrate how they may be used to further advance this area of research. Ultimately, linking policy theories with an organization’s advocacy tactics can uncover how they view policy process and change (Gen & Wright, 2018), and the differences and similarities that may exist across nursing organizations.…”
Section: Policy Advocacy Tactics and Engagement Approachesmentioning
confidence: 99%
“…Research on the 'practice' of civil society engagement takes the form of individual case studies (Adriance, 1994;Barton, 2004;Biruk & Trapence, 2018;Caruso, 2016;Franklin, 2014;Paphitis, 2018;Robins, 2010), case study collections (Barlow & Clarke, 2001;Brecher et al, 2002;Choudry, 2013;Franklin, 2014;Suzuki & Lee, 2015;Warkentin, 2001), theoretical monographs (Buechler, 2000;Laverack, 2013), and edited collections (Maloney & Deth, 2010). There have been a few reports focusing on specific elements of practice (Gen & Wright, 2016;Zoller, 2005) or on movements addressing particular issues (Pianta, 2014) or populations (Smith, 1995).…”
Section: Introductionmentioning
confidence: 99%